2011
DOI: 10.1039/c1jm13336e
|View full text |Cite
|
Sign up to set email alerts
|

Pyrite nanocrystals: shape-controlled synthesis and tunable optical properties via reversible self-assembly

Abstract: Nanocrystals from non-toxic, earth abundant materials have recently received great interest for their potential large-scale application in photovoltaics and photocatalysis. Here, we report for the first time on the shape-controlled and scalable synthesis of phase-pure pyrite (FeS 2 ) nanocrystals employing the simple, inexpensive, thermal reaction of iron-oleylamine complexes with sulfur in oleylamine. Either dendritic nanocrystals (nanodendrites) or nanocubes are obtained by adjusting the iron-oleylamine conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 54 publications
7
80
0
Order By: Relevance
“…These results are very close to our prediction because the thrust of our study was to reduce the bandgap energy of a TiO 2 un-doped system by combining with the FeS 2 nanocrystals. Similarly, a polymer solar cell based on P 3 HT ¼ FeS 2 -NCs was reported 21 and the results showed that a combination of polymer (P 3 HT) and FeS 2 can contribute to an extended photovoltaic response in the red light region similar to literature 36,37 reports that FeS 2 is a narrow bandgap semiconductor (0.95-1.2 eV) showing absorbance across the entire visible region, and presence of sulfur in composite and pure FeS 2 is indicated by a tail broadening of the peak. 25 …”
Section: Optical Spectroscopysupporting
confidence: 53%
“…These results are very close to our prediction because the thrust of our study was to reduce the bandgap energy of a TiO 2 un-doped system by combining with the FeS 2 nanocrystals. Similarly, a polymer solar cell based on P 3 HT ¼ FeS 2 -NCs was reported 21 and the results showed that a combination of polymer (P 3 HT) and FeS 2 can contribute to an extended photovoltaic response in the red light region similar to literature 36,37 reports that FeS 2 is a narrow bandgap semiconductor (0.95-1.2 eV) showing absorbance across the entire visible region, and presence of sulfur in composite and pure FeS 2 is indicated by a tail broadening of the peak. 25 …”
Section: Optical Spectroscopysupporting
confidence: 53%
“…Indirect band gap obtained through the Tauc plot in Fig. 5c, was found to be 1.13 eV and is in accordance with most of the reported values of band gap in pyrite nanomaterials [2,[30][31][32][33][34][35]. The direct band gap may be interpreted from the slope at the absorption edge near 400 nm in the absorption curve to be nearly 2.7 eV.…”
Section: Optical Absorption and Band Gap Determinationsupporting
confidence: 86%
“…The broad, slowly increasing absorption of pyrite NRs reflects the indirect band gap nature of the material [30,31]. Indirect band gap obtained through the Tauc plot in Fig.…”
Section: Optical Absorption and Band Gap Determinationmentioning
confidence: 99%
“…Following injection, the initial iron pyrite monomer concentration is an important role in controlling the shape of iron pyrite. Li et al 67 obtained iron pyrite nanocubes and nanodendrites by adjusting the precursor concentration, which results in different monomer concentration. Ge et al 77 also concluded that increasing the monomer concentration changes the shape of the nal particles from nanocubes to nanoplates and nally to spheres.…”
Section: -69mentioning
confidence: 99%